Due time alert system in oil palm tissue culture laboratory via SMS and email notification: article / Musfirah Mat Som - Mat Som, Musfirah (2011)
Malaysia Palm Oil Board (MPOB) is a government body that responsible for planning, researching and developing the oil palm industry. The culture room must be isolated from the external environment to maintain the appropriate temperature and the relative humidity and to avoid the entrance of contaminants. Cultivars in MPOB are often taking oil palm tissue culture vessel from laboratory. Sometimes, tissue culture vessel is taken and do not return back to the laboratory at the same day. This situation is not good for the growth of tissue culture. By allowing tissue culture at the inappropriate condition, it may cause tissue culture from contaminated by surrounding environment. Therefore, an alert system is required to remind cultivar and administrator to return the tissue culture vessel into the laboratory on the same day before they leave the office. This project is expected to be implemented in oil palm tissue culture department in order to monitor the tissue culture vessel taking in and out from the laboratory. The application of light detector resistor (LDR) in oil palm tissue culture vessel with alert system is the best solution to overcome problems that occurs in MPOB laboratory. Light detector resistor is used in order to detect the present of vessel tissue culture. For this propose the alert system via SMS and email is developed by using SMS Gateway and email server to monitor the tissue culture vessel in laboratory. Once the period of time is exceeded, the cultivar and administrator will trigger via SMS and email. To accomplish this alert system, several open source software such as mail server, SMS Gateway, WAMP is being used. WAMP stands for Apache, MySQL and PHP in Windows. By developing this alert system, it helps to reduce destruction of oil palm tissue culture and maintain the high quality of oil palm.